2021
DOI: 10.3389/fonc.2021.620534
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Carbon Ion Radiotherapy for Meningiomas: A Systematic Review and Meta-Analysis

Abstract: ObjectiveThe purpose of this systematic review and meta-analysis is to evaluate the efficacy and safety of carbon ion radiotherapy (CI-RT) in improving meningioma by comparing photon and protons radiotherapy.MethodsA comprehensive search for relevant studies published until March 17, 2021, was conducted in PubMed, the Cochrane Library, Chinese Biomedical Literature Database and EMBASE. Statistical analyses were performed with R 4.0.3.ResultsWe identified 396 studies, of which 18 studies involving 985 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…During the scoping review, many systematic reviews were found reporting the effectiveness and safety of proton therapy in several indications, such as meningioma of the brain and spinal cord [35,36], skull base chordoma [37], nasopharyngeal cancer [38], intracranial benign tumours [39], and gliomas [40]. However, presented systematic review is the first summary of available evidence about patients with HL or NHL.…”
Section: Discussionmentioning
confidence: 99%
“…During the scoping review, many systematic reviews were found reporting the effectiveness and safety of proton therapy in several indications, such as meningioma of the brain and spinal cord [35,36], skull base chordoma [37], nasopharyngeal cancer [38], intracranial benign tumours [39], and gliomas [40]. However, presented systematic review is the first summary of available evidence about patients with HL or NHL.…”
Section: Discussionmentioning
confidence: 99%
“…Various recent (2020-2023) reviews and other publications consider clinical applications, experience, trials and outcomes for CIRT, some overviewing most or all sites with varying levels of detail 3,4,27,36,38,42,62,[100][101][102] and others discussing single applications only. [103][104][105][106][107][108][109] In 2022, Pompos et al 36 succinctly summarised the clinical indications as: radiation resistant malignancies, such as ACC, mucosal melanoma, NSCLC, liver cancer, bone and soft tissue sarcoma; recurrent previously irradiated cancers (especially rectal cancer), advanced gynaecological malignancies, oesophageal cancer, pancreatic cancer and hypoxic malignancies. For these, XRT and PBT are often not able to deliver sufficient target dose without undue probability of severe toxicity to organs-at-risk.…”
Section: Clinical Indications Patient Numbers and Application To Aust...mentioning
confidence: 99%
“…Various recent (2020–2023) reviews and other publications consider clinical applications, experience, trials and outcomes for CIRT, some overviewing most or all sites with varying levels of detail 3,4,27,36,38,42,62,100–102 and others discussing single applications only 103–109 . In 2022, Pompos et al 36 .…”
Section: Clinical Applications and Experience Of Cirtmentioning
confidence: 99%
“…The diagnosis of meningioma is most common in middle and old age. The frequency increases with age, and women are twice as likely to be diagnosed as men ( 39 , 41 , 42 ).…”
Section: Meningiomasmentioning
confidence: 99%
“…PT is the most common PRT used in clinical practice ( 40 , 42 ). Another option is represented by CIRT, whose use is reserved especially for re-RT after disease progression ( 41 ).…”
Section: Meningiomasmentioning
confidence: 99%